If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -2 + 4i)(x + -2 + -4i) = 0 Reorder the terms: (-2 + X + 4i)(x + -2 + -4i) = 0 Reorder the terms: (-2 + X + 4i)(-2 + -4i + x) = 0 Multiply (-2 + X + 4i) * (-2 + -4i + x) (-2(-2 + -4i + x) + X(-2 + -4i + x) + 4i * (-2 + -4i + x)) = 0 ((-2 * -2 + -4i * -2 + x * -2) + X(-2 + -4i + x) + 4i * (-2 + -4i + x)) = 0 ((4 + 8i + -2x) + X(-2 + -4i + x) + 4i * (-2 + -4i + x)) = 0 (4 + 8i + -2x + (-2 * X + -4i * X + x * X) + 4i * (-2 + -4i + x)) = 0 (4 + 8i + -2x + (-2X + -4iX + xX) + 4i * (-2 + -4i + x)) = 0 (4 + 8i + -2x + -2X + -4iX + xX + (-2 * 4i + -4i * 4i + x * 4i)) = 0 Reorder the terms: (4 + 8i + -2x + -2X + -4iX + xX + (-8i + 4ix + -16i2)) = 0 (4 + 8i + -2x + -2X + -4iX + xX + (-8i + 4ix + -16i2)) = 0 Reorder the terms: (4 + -2X + 8i + -8i + -4iX + 4ix + -16i2 + -2x + xX) = 0 Combine like terms: 8i + -8i = 0 (4 + -2X + 0 + -4iX + 4ix + -16i2 + -2x + xX) = 0 (4 + -2X + -4iX + 4ix + -16i2 + -2x + xX) = 0 Solving 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -2X + -4iX + 4ix + -16i2 + -2x + -4 + xX = 0 + -4 Reorder the terms: 4 + -4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 0 + -4 -2X + -4iX + 4ix + -16i2 + -2x + xX = 0 + -4 Combine like terms: 0 + -4 = -4 -2X + -4iX + 4ix + -16i2 + -2x + xX = -4 Add '-4ix' to each side of the equation. -2X + -4iX + 4ix + -16i2 + -2x + -4ix + xX = -4 + -4ix Reorder the terms: -2X + -4iX + 4ix + -4ix + -16i2 + -2x + xX = -4 + -4ix Combine like terms: 4ix + -4ix = 0 -2X + -4iX + 0 + -16i2 + -2x + xX = -4 + -4ix -2X + -4iX + -16i2 + -2x + xX = -4 + -4ix Add '16i2' to each side of the equation. -2X + -4iX + -16i2 + -2x + 16i2 + xX = -4 + -4ix + 16i2 Reorder the terms: -2X + -4iX + -16i2 + 16i2 + -2x + xX = -4 + -4ix + 16i2 Combine like terms: -16i2 + 16i2 = 0 -2X + -4iX + 0 + -2x + xX = -4 + -4ix + 16i2 -2X + -4iX + -2x + xX = -4 + -4ix + 16i2 Add '2x' to each side of the equation. -2X + -4iX + -2x + 2x + xX = -4 + -4ix + 16i2 + 2x Combine like terms: -2x + 2x = 0 -2X + -4iX + 0 + xX = -4 + -4ix + 16i2 + 2x -2X + -4iX + xX = -4 + -4ix + 16i2 + 2x Reorder the terms: 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = -4 + -4ix + 16i2 + 2x + 4 + 4ix + -16i2 + -2x Reorder the terms: 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = -4 + 4 + -4ix + 4ix + 16i2 + -16i2 + 2x + -2x Combine like terms: -4 + 4 = 0 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 0 + -4ix + 4ix + 16i2 + -16i2 + 2x + -2x 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = -4ix + 4ix + 16i2 + -16i2 + 2x + -2x Combine like terms: -4ix + 4ix = 0 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 0 + 16i2 + -16i2 + 2x + -2x 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 16i2 + -16i2 + 2x + -2x Combine like terms: 16i2 + -16i2 = 0 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 0 + 2x + -2x 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 2x + -2x Combine like terms: 2x + -2x = 0 4 + -2X + -4iX + 4ix + -16i2 + -2x + xX = 0 The solution to this equation could not be determined.
| 12m+3n-5m+10n= | | X*2/3=8/9 | | 9(3b+7)-(7b+2)=-59 | | 10x-5+8x+5=180 | | 9(y+5+3)=108 | | (2x+7i)(2x-7i)= | | f(3)=2f(1) | | A+17=4(A-2)-5+3A | | x^4-7x^3-10x^2+7x+1=0 | | 4x+8=202 | | 8w+5=4(2+1)w | | 0.09xX=77.01 | | C/4=11 | | 13y+7y+(6y+6)=34 | | -6x+-12=42 | | x^2-55x+204=0 | | 0.09xX=62.95 | | 2y+25-19=0 | | 5x+2=x+8T | | 2-3x=-5x+16 | | 6x+13=x+8 | | 5x-4=2(4x+4)-3 | | n/5.5=2 | | 7/8x5/9 | | 2x+5=3(2x-4) | | 7/8x2/9 | | 7x-35=3x+5 | | 7x+5x-3=21 | | y=0.60x+46 | | 2x+122=12x-8 | | 24=86 | | 2(3X-5)=27 |